Understanding Number Line Estimation in Williams Syndrome and Down Syndrome - Simms, V. (J Autism Dev Disord, 2019)
Previous studies suggest that tasks dependent on the mental number line may be difficult for Williams Syndrome (WS) and Down Syndrome (DS) groups. However, few have directly assessed number line estimation in these groups. The current study assessed 28 WS, 25 DS and 25 typically developing (TD) participants in non-verbal intelligence, number familiarity, visuo-spatial skills and number line estimation. Group comparisons indicated no differences in number line estimation. However, the WS group displayed difficulties with visuo-spatial skills and the DS group displayed difficulties with number familiarity. Differential relationships between number line estimation and visuo-spatial/number familiarity skills were observed across groups. Data is discussed in the context of assessment of skills in neurodevelopmental disorders.